Assessing the Catalytic Influence of Modern Information System and Socio-Economic Status on Communities’ Attitude and Awareness to Forest Resource Sustainability in Boki Local Government Area, Nigeria - Iwara, Eja Eja; John O, Ukwetang; Judith E, Otu (Review of Environment and Earth Sciences, 2016)
Man as seriously endangered the forest ecosystem, perhaps due to lack of knowledge on the implications of his activities. This paper assesses the influence of modern information system and socio-economic status, attitude and awareness to forest resource sustainability and conservation in Boki Local Government Areal. Four communities were used of which six hundred copies of questionnaire were administered to residents in the area. The socio-economic status and the modern information dissemination system were captured in the questionnaire. Findings from the data collected show that communities with high socio-economic status have positive attitude and awareness to forest resource conservation and sustainability. This result was affirmed in the tested hypotheses which show a high calculated value greater than the critical value.